Wage and employment determination in volatile times: Sweden 1913-1939 - Bertil Holmlund (Center for Economic Studies and ifo Institute (CESifo), 2012)
The paper studies wage and employment determination in the Swedish business sector from the mid-1910s to the late 1930s. This period includes the boom and bust cycle of the early 1920s as well as the Great Depression of the early 1930s. The events of the early 1920s are particularly intriguing, involving inflation running at an annual rate of 30 percent followed by a period of sharp deflation where nominal wages and prices fell by 30 percent and unemployment increased from 5 to 30 percent. We examine whether relatively standard wage and employment equations can account for the volatile economic development during the interwar years. By and large, the answer is a qualified yes. Industry wages were responsive to industry-specific firm performance, suggesting a significant role for insider forces in wage determination. Unemployment had a strong downward impact on wages. There is evidence that reductions in working time added to wage pressure; yet estimates of labor demand equations suggest that cuts in working time may have slightly increased employment as firms substituted workers for hours.
Keywords: J23; J31; N14; N34; 330; wage determination; labor demand; interwar labor markets